Da liberdade transcendental à liberdade prático moral em Immanuel Kant - Castro, Fagner Menezes (2022)
This research aims to investigate the passing from transcendental freedom to practical moral freedom, from the study of Immanuel Kant’s work: The Critique of Pure Reason (1781) and Groundwork for The Metaphysics of Morals (1785), among others. Firstly, there will be a study about “Transcendental Dialectic” and the process of reason generating its own subjective value knowledge, from where transcendental ideas arise as consequence. There will be a more detailed discussion about the conflict of cosmological ideas, which leads to an antinomy between the series produced by reason and the one produced by understanding over experienced data from the formation of the unconditioned. Within this conflict lies the problem of transcendental freedom i.e., whether it is possible to validly think absolute spontaneity apart from the need of natural causality. For Kant, on the Third Antinomy, it is valid to think logically about absolute spontaneity through dynamic reasoning. Then, in the “Appendix to the Transcendental Dialectics” we start a discussion on regulative principles that differ from mathematical principles. This possibility leads the way for us to think that the maxims of reason are not limited to its theoretical aspect, but also have a regulative use that will be used by practical reason, therefore the ability to generate future maxims is not limited to just one specific aspect of reason. On Groundwork for The Metaphysics of Morals, Kant states that moral common sense may not realize an abstraction such as the Critique of Pure Reason to get to moral acting, for the law of morality already presents itself to common sense and guide its actions indicating the ability to detect right from wrong to the individual.